Cognitive–Linguistic and Constructivist Mnemonic Triggers in Teaching Based on Jerome Bruner’s Thinking - Metsämuuronen, Jari; Räsänen, Pekka (Frontiers in Psychology, 2018)
Effective teachers use mnemonic tools or mnemonic triggers to improve the students’ retention of the study material. This article discusses mnemonic triggers from a theoretical viewpoint based on Jerome S. Bruner’s writings. Fifty small linguistic–cognitive, constructive-, rhetorical-, and phonological mnemonic triggers are detected. These triggers may be the elements our brain use when “constructing the realities” in a Brunerian sense when ordering, differentiating, comparing, and handling information, stories and experiences in our brain. Many of these are small, hidden linguistic elements in speech. This article discusses their usage in the educational talk and textbooks.